2022
DOI: 10.1038/s41598-022-23848-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular electrons transferred from honey probiotic Bacillus circulans inhibits inflammatory acne vulgaris

Abstract: Bacillus circulans (B. circulans) is widely used as an electrogenic bacterium in microbial fuel cell (MFC) technology. This study evaluated whether B. circulans can ferment glucose to generate electricity and mitigate the effects of human skin pathogens. The electricity production of B. circulans was examined by measuring the voltage difference and verified using a ferrozine assay in vitro. To investigate the fermentation effects of B. circulans on inhibition of human skin pathogens, Cutibacterium acnes (C. ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After treatment for 48 h, the mice were euthanized with CO 2 gas, and the ear tissues were obtained for Hematoxylin–Eosin (H&E) and immunofluorescence (IF) staining. The choice of P. acnes induction time and the ADSC treatment time was based on previous research and our preliminary experiments 17 , 18 . This animal experiment was approved by the ethical committee of Tongji Medical College (2022 IACUC Number: 2893) and was performed in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment for 48 h, the mice were euthanized with CO 2 gas, and the ear tissues were obtained for Hematoxylin–Eosin (H&E) and immunofluorescence (IF) staining. The choice of P. acnes induction time and the ADSC treatment time was based on previous research and our preliminary experiments 17 , 18 . This animal experiment was approved by the ethical committee of Tongji Medical College (2022 IACUC Number: 2893) and was performed in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, probiotic applications are also evolving due to the isolation of new and more probiotic strains from a diverse set of samples, and more exhaustive in vitro and in vivo studies. For example, Kao and colleagues examined the extracellular electrons transferred from the honey-derived probiotic, B. circulans, which inhibits the human skin pathogen, C. acnes, by injecting the pathogen intradermally into mice ears to induce an inflammatory response [179]. The results showed that the in vitro B. circulans co-culture enhanced electron production and significantly suppressed C. acnes growth.…”
Section: Postbioticsmentioning
confidence: 99%
“…The results showed that the in vitro B. circulans co-culture enhanced electron production and significantly suppressed C. acnes growth. Moreover, in the in vivo assays of the ears of the Crl:CD1(ICR) mice model, the C. acnes and macrophage inflammatory protein 2 (MIP-2) levels suggested that B. circulans-generated electrons affected C. acnes growth and alleviated the resultant inflammatory response [179]. Islam and colleagues also evaluated a new probiotic strain, B. amyloliquefaciens (BA PMC-80), which exhibited significant anti-C. difficile effects in a co-cultured in vitro assay [180].…”
Section: Postbioticsmentioning
confidence: 99%